Kajian Terjemahan Ungkapan Peribahasa dalam Novel Berjudul Things Fall Apart Karya Chinua Achebe - Elva Hanun Hanifah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This article focuses on analyzing the translation techniques and quality of five proverbs in Chinua Achebe's Things Fall Apart. The study aims to evaluate whether the five proverbs are well translated and whether the translation techniques used are appropriate. Using a qualitative approach, the research analyzes the translations using techniques such as Literal Translation, Dynamic Equivalence and Domestication. The focus is on how the translation is able to preserve the meaning, cultural context, and moral values of the original Igbo proverbs. The accuracy, acceptability and fluency of the translated texts are the main aspects evaluated to identify the effectiveness of the techniques used. In addition, the study examines whether the translation is able to present the original meaning without losing the cultural context contained in the proverbs. The findings provide insights into the challenges of translating culturally sensitive phrases, especially in maintaining the integrity of culturally rich literary texts. Through an in-depth analysis of five proverbs, this article contributes to further understanding of literary translation techniques. It highlights the importance of choosing the right techniques to ensure that cultural and moral values are preserved while producing translations that can be understood by a wide audience.